2009
DOI: 10.1037/a0017046
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment and health among male and female police officers.

Abstract: The aims of this study were to investigate whether sexual harassment is related to mental and physical health of both men and women, and to explore the possible moderating effects of gender on the relation between sexual harassment and health. In addition, we investigated whether women were more often bothered by sexual harassment than men, and whether victims who report being bothered by the harassment experience more health problems compared to victims who did not feel bothered. A representative sample of 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 48 publications
2
53
1
9
Order By: Relevance
“…A study of women in the Swedish military found that sexual harassment predicted psychological distress and decreased mental health (Estrada and Berggren 2009 ). Other mental health problems, like emotional exhaustion and insomnia, were reported by Dutch police women (de Haas et al 2009 ). Studies of Chinese Mainland and Hong Kong Chinese women reported that experiencing sexual harassment is associated with dissatisfaction with one's job and intention to turnover (Chan et al 1999 ;Shaffer et al 2000 ).…”
Section: Implications For Working Women's Wellbeingmentioning
confidence: 94%
“…A study of women in the Swedish military found that sexual harassment predicted psychological distress and decreased mental health (Estrada and Berggren 2009 ). Other mental health problems, like emotional exhaustion and insomnia, were reported by Dutch police women (de Haas et al 2009 ). Studies of Chinese Mainland and Hong Kong Chinese women reported that experiencing sexual harassment is associated with dissatisfaction with one's job and intention to turnover (Chan et al 1999 ;Shaffer et al 2000 ).…”
Section: Implications For Working Women's Wellbeingmentioning
confidence: 94%
“…They also both place critical importance on the welfare and well-being of staff in effectively responding to these pressures. Sexual harassment in the workplace has an acknowledged detrimental effect both on personnel (de Haas, Timmerman and Höing 2009;Holland and Cortina, 2016) and productivity (Dansky and Kilpatrick, 1997). The Police Federation's commissioned surveys find staff noting increased workloads and greater stress burdens.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the Hesketh et al research shows that where police officers feel they have better job conditions, they are prepared to increase their discretionary efforts. De Haas, Timmerman and Höing (2009) concluded sexual harassment in the police environment is a workplace hazard having powerful adverse effects. Their results showed mental and physical health outcomes were experienced by men and women.…”
Section: Sexual Harassment In the Police Servicementioning
confidence: 99%
“…The research that exists finds that, compared with men, women have more negative appraisals of sexual harassment, rating harassment vignettes as more anxiety producing (Berdahl, Magley, & Waldo, 1996) and personal harassment experiences as more bothersome (de Haas, Timmerman, & Höing, 2009). Only one study examined sex differences in the relationship between appraisal and outcomes: de Haas and colleagues (2009) found no differences in the mental and physical health of male and female police officers who reported sexual harassment that they perceived to be bothersome.…”
Section: Sex Differences In Sexual Harassment Appraisal Processesmentioning
confidence: 99%